2012
DOI: 10.1371/journal.pone.0039366
|View full text |Cite
|
Sign up to set email alerts
|

Saponin Inhibits Hepatitis C Virus Propagation by Up-regulating Suppressor of Cytokine Signaling 2

Abstract: Saponins are a group of naturally occurring plant glycosides which possess a wide range of pharmacological properties, including anti-tumorigenic and antiviral activities. To investigate whether saponin has anti-hepatitis C virus (HCV) activity, we examined the effect of saponin on HCV replication. HCV replication was efficiently inhibited at a concentration of 10 µg/ml of saponin in cell culture grown HCV (HCVcc)-infected cells. Inhibitory effect of saponin on HCV replication was verified by quantitative real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…post vaccination as shown in (fig.6). The results agreeable with (Lee et al, 2012) who tested inhibitory effect of saponin on Hepatitis C virus (HCV) replication by qRT-PCR. Also, no any clinical signs of BEF were observed during the whole examination intervals, the body temperature was elevated in all vaccinated animals in range 0.5 o C after one-day post inoculation and then return to the normal temperature.…”
Section: Discussionsupporting
confidence: 87%
“…post vaccination as shown in (fig.6). The results agreeable with (Lee et al, 2012) who tested inhibitory effect of saponin on Hepatitis C virus (HCV) replication by qRT-PCR. Also, no any clinical signs of BEF were observed during the whole examination intervals, the body temperature was elevated in all vaccinated animals in range 0.5 o C after one-day post inoculation and then return to the normal temperature.…”
Section: Discussionsupporting
confidence: 87%
“…They are reported to have a wide range of pharmacological properties that exert various benefits, such as anti-inflammatory and anti-diabetic properties (Lee et al, 2012).…”
Section: Quick Assays For Presence Of Phytochemical Compoundsmentioning
confidence: 99%
“…(2015b) andVahedi et al (2017) in beluga treated with onion and ginger, respectively(Akrami et al 2015b; Vahedi et al 2017).Moreover, mushroom extract did not remarkably affect on triglyceride and lipid in comparison with the control. However, the lowest value of triglyceride and lipid were observed in 2% mushroom extract treatment.The reduction of triglycerides could depend on saponin exist in fungus as described in(Lee, Lim, Kang, Min, Son, Lee, Park, Ngo, Tran, Lim & Hwang 2012). Conversely, Akrami et al(2015b) demonstrated that the use of 1% onion powder in beluga diet decreased the amount of triglyceride significantly in comparison with the control.…”
mentioning
confidence: 98%